2012
DOI: 10.1371/journal.pone.0052486
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Direct Reverse Transcription Loop-Mediated Isothermal Amplification Method without RNA Extraction for the Detection of Human Enterovirus 71 Subgenotype C4 in Nasopharyngeal Swab Specimens

Abstract: Human enterovirus 71 (EV71) is the major causative agent of hand, foot, and mouth disease (HFMD) worldwide and has been associated with neurological complications which resulted in fatalities during recent outbreak in Asia pacific region. A direct reverse transcription loop-mediated isothermal amplification (direct RT-LAMP) assay using heat-treated samples without RNA extraction was developed and evaluated for the detection of EV71 subgenotype C4 in nasopharyngeal swab specimens. The analytical sensitivity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 27 publications
1
45
0
Order By: Relevance
“…The only limitation of RT-LAMP is the extraction of RNA under field conditions. However, Fukuta et al (17) and Nie et al (18) reported that RT-LAMP can be performed on crude samples without RNA extraction. The crude samples were not tested by RT-LAMP in this study, but this could be a better option and it may replace the other diagnostic tests in the field.…”
Section: Discussionmentioning
confidence: 99%
“…The only limitation of RT-LAMP is the extraction of RNA under field conditions. However, Fukuta et al (17) and Nie et al (18) reported that RT-LAMP can be performed on crude samples without RNA extraction. The crude samples were not tested by RT-LAMP in this study, but this could be a better option and it may replace the other diagnostic tests in the field.…”
Section: Discussionmentioning
confidence: 99%
“…GQ279371.1) from the GenBank database (http: //www.ncbi.nlm.nih.gov/) were used to design the primers for the EV71 and CVA16 RT-IMSA assays, respectively. These sequence regions selected were highly conserved regions of the EV71 and CVA16 VP1 genes, which were used and evaluated previously in our laboratory for the primer designs for the RT-LAMP assay (4,18,23). The primer design for the RT-IMSA assay was mainly based on the rules for that of the RT-LAMP assay, with the aid of PrimerExplorer V4 (see http://primerexplorer.jp /elamp4.0.0/; Eiken, Kyoto, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…It is difficult to achieve rapid detection using traditional virus isolation and neutralization because of their low specificities and detection limits, as well as the long time that is spent obtaining results (4)(5)(6). Nucleic acid amplification techniques, such as reverse transcription-PCR (RT-PCR) (7)(8)(9) and reverse transcription-quantitative PCR (qRT-PCR) (10, 11) take less time (2 to 3 h) and are generally used for making a standard diagnosis due to a high detection limit.…”
mentioning
confidence: 99%
“…In addition, it has been reported that the sensitivity of molecular detection methods such as qPCR and LAMP is subject to a variety of factors present in clinical samples. For example, the multitude of drugs and fluids prescribed to patients at risk for IA can inhibit the qPCRs (36), while in comparison, the Bst polymerase in LAMP is more tolerant to these inhibitors than Taq polymerase in the amplification of the clinical samples (37), which might lead to better sensitivity for the LAMP assay.…”
Section: Discussionmentioning
confidence: 99%